Facilitating Knowledge of Women on Importance of Iodine in Foetal Brain Development through Nursing Education: An Evidence-Based Educational Intervention - ABRAHAM, BINDU KAIPPARETTU (International Journal of Innovative Research in Medical Science, 2018)
The purpose of the evidence-based practice educational intervention was to a) assess the knowledge of women on the importance of iodine in fetal brain development b) find the effectiveness of planned teaching program on women. Iodine Deficiency Disorders can impact on people of all ages, but most severely on the baby while it is developing in the womb. During pregnancy, it can cause maternal and fetal hypothyroidism and impair neurological development of the fetus. This study showed that women did not have enough knowledge regarding the importance of iodine in fetal brain development. So there was lack of knowledge in some aspects regarding the importance of iodine in fetal brain development among women residing in the rural area The nurses have an influential role in imparting knowledge on the importance of iodine in fetal brain development. They can utilize their opportunities to spread awareness about the importance of iodine deficiency disorders leading to brain damage. Providing EBP educational intervention on this topic positively impacted on their knowledge. The findings underscore evidence-based nursing is one approach that may enable future healthcare providers to manage the explosion of new literature and technology and ultimately may result in improved patient outcomes. Hence it helps to implement in their caregiving as a nurse educator, midwife, and as public health nurse.